Hydrothermal Synthesis of Li2MnO3-Stabilized LiMnO2 as a Cathode Material for Li-Ion Battery. (12th July 2021) - Vu, Ngoc Hung; Dao, Van-Duong; Vu, Hong Ha Thi; Van Noi, Nguyen; Tran, Dinh Trinh; Ha, Minh Ngoc; Pham, Thanh-Dong
Abstract : Herein, we reported the composite structure of LiMnO2 and Li2 MnO3 as a low-cost and environmentally benign cathode material. This composite with the main phase of LiMnO2 (90%) was synthesized by hydrothermal method at 220°C from LiOH and Mn(CH3 COO)2 precursors. The obtained nanosized LiMnO2 -LiMnO3 cathode material exhibits a high capacity of 265 mAh g -1 at C/10. The incorporation of Li2 MnO3 into the LiMnO2 phase could stabilize the structure, leading to the improved cycle stability of the cathode. The capacity retention of the cathode was 93% after 80 cycles at C/2. Our results facilitate a potential strategy for developing high-performance cathode materials based on the Li-Mn-O system.